Approximation of the classes S^r_p,θB(R^d) of functions of many variables by entire functions of a special form - Yanchenko, S. Ya. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
Exact-order estimates are obtained for the approximations of the functional classes S^r_p,θB(R^d) by entire functions of a special form.